Anatomy of Infraorbital Foramen: Influence of Sex, Side, and Cranium Size. Issue 4 (June 2019) - Gibelli, Daniele; Borlando, Alessia; Barni, Luisa; Sartori, Patrizia; Cappella, Annalisa; Pucciarelli, Valentina; Cattaneo, Cristina; Sforza, Chiarella
Abstract : Abstract: Several researchers have analyzed the collocation of infraorbital foramen, but no study has so far considered the possible influence of cranial size. Three measurements (distances from anterior nasal spine, inferior orbital rim, angle at the intersection between the line from anterior nasal spine and the transversal plane parallel to the Frankfurt plane) were taken on 100 skulls belonging to a contemporary skeletal collection. In addition, maximum cranial length, maximum cranial breadth, cranial height, and bizygomatic breadth were measured, together with 2 indices (horizontal cephalic index and Giardina Y-index). Differences according to sex and side were assessed through 2-way analysis of variance test ( P <0.05). Measurements showing statistically significant differences according to sex were further assessed through 1-way analysis of covariance test including cranial measurements and indices as covariates ( P <0.05). Statistically significant differences according to sex and side were found respectively for the distance from anterior nasal spine and the angle at infraorbital foramen ( P <0.05). One-way analysis of covariance test verified that the sexual dimorphism of infraorbital foramen- anterior nasal spine distance was independent from the general measurements of cranium. The present study first proved that sexually dimorphic parameters useful for the localization of infraorbital foramen do not depend upon the cranium size.